ANALISIS KEBIJAKAN DOKUMEN RKK PENAWARAN PADA PT X DENGAN MENGGUNAKAN SISTEM INTERNATIONAL SUSTAINABILITY RATING SYSTEMS (ISRS) SEBAGAI MENINGKATKAN KINERJA KESELAMATANKONSTRUKSI SUBCONTRACTOR - Sandhy Cahyadi; Baiduri Widanarko; Rossy Armyn Machfudiyanto (Universitas Pahlawan, 2022)
The root causes of most industrial accidents have been linked to process safety issues ranging from poor safety culture, lack of communication, asset integrity issues, lack of management leadership and human factors as well as inappropriate policies. This accident can be prevented with adequate application of process safety management (PSM). The process of selecting a Subcontractor, who will be appointed in a job, is the first step to run a company system as prevention, supervision, implementation and quality improvement in a job. In this research conducted by Delphi. This research was conducted from February 2022 to June 2022. Data collection techniques were through direct observation and review of company documents guided by RKK offers which will be analyzed according to the guidelines of the International Sustainable Rating System (ISRS). Another goal is that if this policy document is carried out in a more appropriate manner, then it is certain that it can improve the diving performance of subcontractor construction and from the government side so that the Ministry of Public Works and Public Housing can form an assessor team during the initial vendor selection inspection, and further develop the points which can cover to ensure that the subcontractor or vendor has carried out document policies in accordance with the rules of the applicable International Sustainability Rating System (ISRS). And for the company to be able to display an increase in construction safety performance.